Construction of ternary diagram for liquid-liquid extraction process using computer-based program - Sulayman, A. A.; Araromi, D. O.; Ayodeji, O. S.; Salam, K. K. (LAUTECH Journal of Engineering and Technology, 2024)
The Liquid-Liquid Extraction (LLE) is a liquid-liquid phase mass transfer process in which solute chemicals are transferred between two immiscible or partially miscible liquids due to difference in solubility of the solutes in the two liquids. The phase equilibrium relationships are generally inconvenient to handle algebraically, therefore, LLE computational analyses are usually made graphically. Manual construction of ternary diagram becomes cumbersome, tedious and time consuming when used for a process that requires large number of stages. Therefore, the aim of this work was to develop a customized computer package for the ternary diagram. The customized computer package for the ternary diagram construction was achieved with the use of fuzzy inference system toolbox and primitive line function in MATLAB. The computer program was test-run using data from literature to determine theoretical number of stages for a given LLE separation process. The result compared well with the existing literature result.